2011
DOI: 10.2514/1.55134
|View full text |Cite
|
Sign up to set email alerts
|

Overtip Choking and Its Implications on Turbine Blade-Tip Aerodynamic Performance

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Experimentally, Zhang et al [26] illustrated that the local heat transfer was directly affected by shock waves in a striped pattern within the tip gap. Zhang and He [27] also explored the differences of low and high-speed flows noting the difference in flow structures and tip leakage loss. Comparable findings were presented by Shyam et al.…”
mentioning
confidence: 99%
“…Experimentally, Zhang et al [26] illustrated that the local heat transfer was directly affected by shock waves in a striped pattern within the tip gap. Zhang and He [27] also explored the differences of low and high-speed flows noting the difference in flow structures and tip leakage loss. Comparable findings were presented by Shyam et al.…”
mentioning
confidence: 99%
“…The chocking behaviour of the tip flow and the formation of the shockwave system within the tip gap were also studied by Harvey, 33 Molter et al, 34 and Zhange and He. 35 Tip leakage flow development exposes the tip surface to very high heat load. This erodes the sharp edges of the tip a while after being in operation and results into thermal damages such as in-service burn out.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the full squealer case can decrease the total pressure loss due to the TLV. Zhang and He (2011) conducted a computational analysis of overtip choking flow on the high-pressure turbine blade at a transonic condition and focused on the flow behavior and the generation mechanisms of tip leakage loss. The flow distribution within the tip gap clearly illustrates the choked tip flow, which can block the overtip flow because of the influence of suction-surface side.…”
Section: Introductionmentioning
confidence: 99%